IMPROVING TEACHER ABILITY IN CLASSROOM MANAGEMENT POST COVID-19 PANDEMIC AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL, PANGARANGAN SUMENEP - Asmoni Asmoni; Mas’odi Mas’odi; Hodairiyah Hodairiyah (Proceeding International Conference on Digital Education and Social Science, 2022)
The covid pandemic is one of the important impacts in learning, because learning during the covid pandemic by online. Over time, this period underwent a gradual transition. This transition is called the post-pandemic. At that time, the learning process in the classroom is offline. Thus, this study aims to describe the efforts and strategies carried out by classroom teachers in improving teacher skills in classroom management after the COVID-19 pandemic at the Integrated Islamic Elementary School in Sumenep Regency. The method used in this research was descriptive qualitative with interview technique. While the data obtained in the form of sentences and paragraphs from the interviews. The result of this study is strategy to improve the ability of teachers and create a more optimal teaching and learning process after the covid-19 pandemic. The research on classroom management after the COVID-19 pandemic in integrated Islamic elementary schools can be an illustration and example for teachers to be applied in the school.